Cycle Sequencing Protocol Using Deep VentR® (exo-) DNA Polymerase and Reduced dNTP and [α-35S]dATP Concentrations - Bernard Mariamé (BioTechniques)
Benchmarks are brief communications that describe helpful hints, shortcuts, techniques or substantive modifications of existing methods.